Kajian Strategi Pemberdayaan UMKM Dalam Menghadapi Perdagangan Bebas Kawasan ASEAN (Studi Kasus Kampung Batik Laweyan) - Alief Rakhman Setyanto; Bhimo Rizky Samodra; Yogi Pasca Pratama (ETIKONOMI, 2015)
The Empowerment Strategy of Micro and Small Enterprise in Facing ASEAN Free Trade (Case Study at Kampung Batik Laweyan)National economics development in Indonesia. Which became priority are micro, small, and medium enterprises. (UMKM ) would become the backbone of the economic society based to reduce the poverty and development bases to broaden economic and would give significant contribution in improving regional economy and national economic resilience. Batik to UMKM laweyan can survive in the current free trade it is required a pattern the right strategy. In the research uses a qualitative methodology with data. Colecction method interview, participant observation and study documentation. Then data analysis technique in this researh using data clecction, the reduction of the data , display data and thr concludion of the data analysis. The results of reaarch sugested that small and medium business UMKM development pattern batik Laweyan with inovation renew the product then applying social capital by multiplying tissues business ecosystem.DOI: 10.15408/etk.v14i2.2271